The impact of closed ICU model on mortality in general surgical intensive care unit - Kaweesak Chittawatanarat (2018)
Background: A closed model of ICU (intensive care unit) care is associated with improved outcomes and less resource utilization in mixed medical and surgical ICUs as well as traumatic ICUs. However, most of ICUs in developing countries use an opened model especially in surgical ICUs due to lack of specialized physician. The aims of the present are to compare the effects of closed and opened model on ICU mortality and length of ICU stay. Material and Method: The authors conducted a retrospective study to compare mortality between two periods of time. First period was between July 2002 and June 2004, and used open model. The second period was between July 2004 and June 2006, and followed by closed model. The closed model was defined as an ICU service led and managed by an intensivist. The open model was an ICU service where critically ill surgical patients were managed by host surgeons individually. Result: Two thousand two hundred and sixty nine patients were included in the present (Open vs. Close, 1,038 vs. 1,231). The overall ICU mortality rate was decreased with statistical significance in closed model (27.4% vs. 23.4%; p = 0.03). This effect was obvious in patients admitted to ICU longer than 48 hours (22.7% vs. 13.9%; p < 0.01). After adjusting for differences in baseline characteristics and case-mix factor, the risk of death in closed ICU model was also statistically significant less than opened model [RR = 0.85 (0.74-0.98); p = 0.02]. The effect was explicit in patients admitted to ICU longer than 48 hours [RR = 0.60 (0.47-0.76); p < 0.01]. However, risk of death in non-traumatic patients and elderly patients older than 65 years of age tend to be lower in closed model [RR = 0.81 (0.64-1.01); p = 0.06 and RR = 0.81 (0.64-1.01); p = 0.07 respectively]. In addition, closed model ICU has shorter length of ICU stay (5.4 ± 7.1 vs. 4.6 ± 6.1 days; p < 0.01) and adjusted length of ICU stay was lowered about 0.80 day [-0.80 day (-1.34 to -0.25); p < 0.01] in closed model with statistical significance when compare to open model. Conclusion: The closed model, led and managed by an intensivist, is associated with reduction in overall ICU mortality and has greatest effect in patients admitted longer than 48 hours. Furthermore, this model shortens ICU length of stay.